Geochemical mapping of urban soils in Athens, Greece - Preliminary results - Argyraki, A.; Kelepertzis, E.; Fligos, G.; Athanasiou, E.; Gardiakos, K.; Kourgia, V. (Bulletin of the Geological Society of Greece, 2013)
Urban geochemistry is a fast growing scientific discipline mainly because of the profound impact of large cities on the environment as well as the increase in the world’s urban population. The present study aims to produce the urban geochemical map of Athens, based on multi-element analysis of surface soils (0-10 cm) with emphasis in the spatial distribution of potentially harmful elements (PHEs). Soil sampling was based on a regular 1km x 1km grid, laid over the survey area covering more than 200 km2. Sampling locations within the grid cells were selected giving priority to playgrounds, schools and urban parks. The < 100 μm fraction of a total of 320 soil samples were analysed by Flame Atomic Absorption Spectroscopy for Pb, Zn, Cu, Cd, Cr, Ni, Co and Mn after aqua regia dissolution. Average content of Pb (62 mg/kg), Cu (36 mg/kg), Zn (91 mg/kg) and Mn (465 mg/kg) in soil was lower than reported concentrations from other European cities while Cr (74 mg/kg), Ni (89 mg/kg) and Co (16 mg/kg) were relatively enriched. Geochemical maps were plotted within GIS enabling recognition of spatial trends in elemental concentrations and potential sources of the elements. The research outcome will contribute to the evaluation of quality characteristics of urban soils in Athens and drive attention to areas of any environmental or health risks.